Neural Correlates of Working Memory Deficits in Different Adult Outcomes of ADHD: An Event-Related Potential Study - Zhao, Xixi; Li, Hui; Wang, Encong; Luo, Xiangsheng; Han, Chuanliang; Cao, Qingjiu; Liu, Lu; Chen, Jin; Wang, Changming; Johnstone, Stuart J.; Wang, Yufeng; Sun, Li (Frontiers in Psychiatry, 2020)
Abstract Background: We investigated WM processing in a longitudinal sample of young adults with persistent and remittent childhood-onset ADHD to examine neural correlates of working memory related to adult outcomes of ADHD. Methods: Forty-seven Chinese young adults who had been diagnosed with ADHD in childhood received follow-up assessments for an average of 9 years. The ADHD sample consists 25ADHD persisters (Mean age =18.38 ± 0.5 years) and 22 remitters (Mean age = 18.78 ± 1.10) were compared with 25 sex ratio and IQ matched healthy adults (Mean age = 19.60 ± 1.22) during a verbal n-back task. Results: No differences in behavioral measures were observed between the three groups. Compared with healthy controls, the N1 amplitudes of ADHD persisters and remitters were larger, and the P2 amplitudes of persisters and remitters were smaller, while no significant differences between the persister and remitter groups were observed. The P3 amplitudes of the remitter and control groups were higher than those in the persistence group, but there was no significant difference between remitters and healthy controls. Conclusion: P3 amplitudes reflecting post-decisional processing and/or updating of WM were sensitive to ADHD remission, improving concurrently with ADHD symptoms. These results indicate that N1, P2, and P3 components during WM processing might be potential biomarkers for identifying different ADHD outcomes.